The synedochic polyacroasis in the poetry of César Vallejo (Castilla. Estudios de Literatura, 2026)
This article analyzes three poems by the Peruvian writer César Vallejo: “III” (from Trilce), “Himno a los voluntarios de la República” (from España, aparta de mí este cáliz) and “Telúrica y magnética” (Poemas humanos), which correspond to three different moments of his literary production and his worldview. The hypothesis to be demonstrated is that, in these texts, there is a gradient through which one starts from an Andean family community towards an enlarged community that exceeds the national and human. For the analysis, we base on theoretical approaches about polyacroasis (Tomás Albaladejo), as well as embodied cognition (Victor Bermúdez and Friederike Foedtke) and the notion of community (Benedict Anderson and Zygmunt Bauman). In this sense, Vallejo’s poetry allows questioning the merely rational paradigm in order to access a heterogeneous and dialogic community where the body plays a fundamental role as motor of knowledge.
Keywords: Peruvian poetry; César Vallejo; community; polyacroasis; embodied cognition